2020
DOI: 10.3892/or.2020.7547
|View full text |Cite
|
Sign up to set email alerts
|

miR‑10a increases the cisplatin resistance of lung adenocarcinoma circulating tumor cells via targeting PIK3CA in the PI3K/Akt pathway

Abstract: Circulating tumor cells (CTCs) that are shed from the primary tumor invade the blood stream or surrounding parenchyma to form new tumors. The present study aimed to explore the underlying mechanism of cisplatin resistance in lung adenocarcinoma CTCs and provide clinical treatment guidance for lung cancer treatment. CTCs from the blood samples of 6 lung adenocarcinoma patients were treated with different concentrations of cisplatin along with A549 and H1299 cells. The sensitivity of CTCs to cisplatin was explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…PIK3CA locates on chromosome 3 and encodes the p110α catalytic subunit of PI3K, which can enhance cell activity and tumour formation via positively regulating PI3K/Akt activity [9]. PIK3CA regulates the generation of phosphatidylinositol triphosphate to activate Akt/PKB kinase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PIK3CA locates on chromosome 3 and encodes the p110α catalytic subunit of PI3K, which can enhance cell activity and tumour formation via positively regulating PI3K/Akt activity [9]. PIK3CA regulates the generation of phosphatidylinositol triphosphate to activate Akt/PKB kinase.…”
Section: Discussionmentioning
confidence: 99%
“…As is widely known, the phosphatidylinositol 3-kinase (PI3K)/Akt pathway is involved in physiological processes underlying a variety of biological reactions, including inflammation and apoptosis [7,8]. As a target gene of miR-10a, the PI3K p100 catalytic subunit α (PIK3CA) plays a critical role in the cisplatin resistance of lung adenocarcinoma circulating tumor cells via the in PI3K/Akt pathway [9]. Many studies have reported that hypoxia-reoxygenation (H/R) injury can activate the PI3K/Akt pathway to protect renal tubular epithelial cells [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-10a expression promotes the metastatic behavior of pancreatic tumor cells and its repression is sufficient to inhibit invasion and metastasis formation [ 36 ]. The downregulation of miR-10a in chronic myeloid leukemia CD34+ cells increases USF2-mediated cell growth [ 37 ] and increases the cisplatin resistance of lung adenocarcinoma circulating tumor cells via targeting PIK3CA in the PI3K/Akt pathway [ 38 ]. MiR-26a can function not only as tumor suppressor but also as an oncogenic miRNA; its function is tumor type-specific and highly dependent on its targets in different cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…et al, 2016 ). To contribute to Akt activation and DDP-resistance, PI3K also is targeted by miR-10a ( Huang T. et al, 2020 ). In the same way, two downstream effectors of the PI3K/Akt pathway are also regulated by miRs.…”
Section: Micrornas Involved In Ddp-chemoresistancementioning
confidence: 99%